A Comparative Study of Entrance in Traditional and Contemporary Houses of Iran - Dehbandi, Ramin; Einifar, alireza; Cheragh makani, Helaleh (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2017)
In contemporary houses in Iran, because of changes in the methods of designing and building houses, importance of entrance reduced to such level that now in contemporary houses entrance is just a door. Entrance correlates indoor safe space of house and outdoors. It`s importance lays in controlling entry, exit, territory and hierarchy. Since house owners were satisfied with traditional form of entrance, it is a good idea to learn from them in designing new entrances. The purpose of this research is to find a way for designing appropriate entrances for Iranian contemporary houses. To do this at first 40 traditional houses and 40 contemporary houses in Isfahan and Kashan were selected. These two cities are from margin of desert and the origin of traditional houses of Iran. Analysis showed that blockage of visual and phonic relation, creating a space between outdoor public space and indoor private space, creating access patterns to internal spaces and traits that separate in and out were the most significant properties of traditional entrances. All these traits are ignored in contemporary entrances. Suggestions made for design include creating public meeting space in yard and creating a separate entrance space for each house in apartments.